Monetary policy and uncertainty in an empirical small open economy model - Alejandro Justiniano; Bruce Preston (Federal Reserve Bank of Chicago, 2008)
This paper explores optimal policy design in an estimated model of three small open economies: Australia, Canada and New Zealand. Within a class of generalized Taylor rules, we show that to stabilize a weighted objective of output, consumer price inflation and nominal interest variation optimal policy does not respond to the nominal exchange. This is despite the presence of local currency pricing and due, in large part, to observed exchange rate disconnect in these economies. Optimal policies that account for the uncertainty of model estimates, as captured by the parameters' posterior distribution, similarly exhibit a lack of exchange rate response. In contrast to Brainard (1967), the presence of parameter uncertainty can lead to more or less aggressive policy responses, depending on the model at hand.
Keywords: 330